The formation of ultra-fine particles during ozone-initiated oxidations with terpenes emitted from natural paint - Lamorena, Rheo B.; Jung, Sang-Guen; Bae, Gwi-Nam; Lee, Woojin (ELSEVIER, 2007)
The formation of secondary products during the ozone-initiated oxidations with biogenic VOCs emitted from natural paint was investigated in this study. Mass spectrometry and infrared spectroscopy measurements have shown that the major components of gas-phase chemicals emitted from natural paint are monoterpenes including alpha- and beta-pinenes, camphene, p-cymene, and limonene. A significant formation of gaseous carbonyl products and nano-sized particles (4.4-168 nm) was observed in the presence of ozone. Carboxylic acids were also observed to form during the reactions (i.e. formic acid at 0.170ppm and acetic acid at 0.260ppm). The formation of particles increased as the volume of paint introduced into a reaction chamber increased. A secondary increase in the particle number concentration was observed after 440 min, which suggests further partitioning of oxidation products (i.e. carboxylic acids) into the particles previously existing in the reaction chamber. The growth of particles increased as the mean particle diameter and particle mass concentrations increased during the reaction. The experimental results obtained in this study may provide insight into the potential exposure of occupants to irritating chemical compounds formed during the oxidations of biogenic VOCs emitted from natural paint in indoor environments. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ORGANIC AEROSOLS; INDOOR AIR; GAS; OZONOLYSIS; EMISSIONS; CHEMISTRY; PRODUCTS; ACIDS